Crystal orientation, crystallinity, and thermoelectric properties of Bi0.9Sr0.1CuSeO epitaxial films grown by pulsed laser deposition. (9th January 2018) - Ishizawa, Mamoru; Fujishiro, Hiroyuki; Naito, Tomoyuki; Ito, Akihiko; Goto, Takashi
Abstract: We have grown Bi0.9 Sr0.1 CuSeO epitaxial thin films on MgO and SrTiO3 (STO) single-crystal substrates by pulsed laser deposition (PLD) under various growth conditions, and investigated the crystal orientation, crystallinity, chemical composition, and thermoelectric properties of the films. The optimization of the growth conditions was realized in the film grown on MgO at the temperature T s = 573 K and Ar pressure P Ar = 0.01 Torr in this study, in which there was no misalignment apart from the c -axis and no impurity phase. It was clearly found that the higher crystal orientation of the epitaxial film grown at a higher temperature under a lower Ar pressure mainly enhanced the thermoelectric power factor P (= S 2 /ρ), where S is the Seebeck coefficient and ρ is the electrical resistivity. However, the thermoelectric properties of the films were lower than those of polycrystalline bulk because of lattice distortion from lattice mismatch, a low crystallinity caused by a lower T s, and Bi and Cu deficiencies in the films.